Antioxidant phenolics of Justicia adhatoda L. and Cordia dichotoma Frost. Promote thrombolytic activity through binding to a serine protease, tissue plasminogen activator protein - Annika Maria Paul; Anish Nag (Biomedical and Biotechnology Research Journal, 2023)
Background: The tissue plasminogen activator (tPA) protein dissolutes fibrin clots and prevents the disease like thrombosis. The current study aimed to study the tPA-promoting activity of bioactive molecules of Justicia adhatoda L (JA) and Cordia dichotoma Frost (CD). Methods: The phytochemical characterization of methanolic and aqueous extracts of JA and CD stems was performed through qualitative analysis, Fourier-transform infrared spectroscopy (FTIR), and biochemical tests (total phenolic and total flavonoid content [TPC and TFC]). The bioactivity of the extracts was studied through total antioxidant capacity (TAC) and ferric-reducing antioxidant potential (FRAP) assays. Finally, forty phytocompounds from JA and CD were identified from the literature, and in silico molecular docking study was performed to target tPA protein (PDB id 1A5H, Chain A, X-ray diffraction, resolution 2.90 Å). Results: Various phytochemical classes were identified from extracts, through qualitative and FTIR analysis. TPC and TFC were estimated from the JA and CD extracts within the range of 9.34–28.67 mg gallic acid equivalent/100 g of extract weight (EW) and 2.48–16.17 mg quercetin equivalent/100 g of EW, respectively. The aqueous extract of CD showed the highest TAC of 14.90 ascorbic acid equivalent (AAE)/100 g of EW, and the methanolic extract of JA had the highest FRAP activity of 27.77 mg AAE/100 g EW. The molecular docking study showed that apigenin 6,8-di-glucopyranoside had the highest binding potential toward the tPA (−9.380 kcal/mol). Conclusion: It can be concluded that antioxidant phytochemicals of JA and CD could promote the tPA activity, thereby promoting thrombolytic activity.